2021
DOI: 10.3390/geriatrics6030063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Demographic and Health Dynamics on Cognitive Status in Mexico between 2001 and 2015: Evidence from the Mexican Health and Aging Study

Abstract: Sources of health disparities such as educational attainment, cardiovascular risk factors, and access to health care affect cognitive impairment among older adults. To examine the extent to which these counteracting changes affect cognitive aging over time among Mexican older adults, we examine how sociodemographic factors, cardiovascular diseases, and their treatment relate to changes in cognitive function of Mexican adults aged 60 and older between 2001 and 2015. Self and proxy respondents were classified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
2
15
0
2
Order By: Relevance
“…Although five articles were classified as unclear regarding the appropriateness of recruited participants ( Brucki and Nitrini, 2014 , Correia et al, 2011 , Lopes et al, 2012 , Pedraza et al, 2017 , Ramos-Cerqueira et al, 2005 ), all articles presented adequate sample size. Further, in 10 studies, it was not clear whether dementia was assessed in a standardised way, i.e., whether those involved in data collection were trained in the use of the instruments ( Albala et al, 1997 ; Eldemire-Shearer et al, 2018 ; Magalhães et al, 2008 ; Martínez Querol et al, 2005 ; Mejia-Arango and Gutierrez, 2011 ; Mejia-Arango et al, 2021 ; Neita et al, 2014 ; Pedraza et al, 2017 ; Sanchez-Arenas et al, 2013 ; Villarreal et al, 2016 ). Finally, Soto-Añari et al (2021) included a non-probabilistic sampling obtained by convenience samples from private and public clinics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although five articles were classified as unclear regarding the appropriateness of recruited participants ( Brucki and Nitrini, 2014 , Correia et al, 2011 , Lopes et al, 2012 , Pedraza et al, 2017 , Ramos-Cerqueira et al, 2005 ), all articles presented adequate sample size. Further, in 10 studies, it was not clear whether dementia was assessed in a standardised way, i.e., whether those involved in data collection were trained in the use of the instruments ( Albala et al, 1997 ; Eldemire-Shearer et al, 2018 ; Magalhães et al, 2008 ; Martínez Querol et al, 2005 ; Mejia-Arango and Gutierrez, 2011 ; Mejia-Arango et al, 2021 ; Neita et al, 2014 ; Pedraza et al, 2017 ; Sanchez-Arenas et al, 2013 ; Villarreal et al, 2016 ). Finally, Soto-Añari et al (2021) included a non-probabilistic sampling obtained by convenience samples from private and public clinics.…”
Section: Resultsmentioning
confidence: 99%
“…The diamonds represent the prevalence of all-cause dementia for studies with representative samples, the horizontal bars the 95% confidence intervals. Note: ES: effect size; CI: confidence intervals; * Additional information retrieved from Mejia-Arango et al (2021) .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Life-course sociodemographic and health-related conditions can change cognitive profiles of old adults participating in these types of studies across different age cohorts. Mejía-Arango et al (2021) [ 2 ] used data from the 2001 and 2015 years of the Mexican Health and Aging Study (MHAS) to study trends in cognitive impairment and dementia for Mexican older adults aged 60 years or older. They found a higher likelihood of dementia and a lower likelihood of cognitive impairment no dementia (CIND) in 2015 compared to 2001.…”
mentioning
confidence: 99%
“…In recent decades, the incidence of (mild) cognitive impairment has generally been stable [7,8] or decreased [9][10][11]. Three studies of this incidence involved assessment at more than two timepoints; one showed a decreasing incidence of cognitive impairment [Mini-Mental State Examination (MMSE) score < 18] among ≥ 60-year-olds (≥80 years: 77%) in China during 1998-2014 [9], and the other two showed stable trends of the incidence of mild cognitive impairment during 2015-2019 among ≥ 65-year-olds in Germany [7] and during 1993-2016 among ≥ 70-year-olds in the US, with no difference among birth cohorts over the range 1899-1946 [8].…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%